First Report of Atherigona orientalis (Diptera: Muscidae) infesting Capsicum annuum in West Sumatra, Indonesia confirmed by COI barcoding - Nguyễn Phước Sang; Novri Nelly; Reflinaldon Reflinaldon; Hidrayani Hidrayani (Universitas Lampung, 2026)
Accurate identification of pest species is fundamental to the development of effective integrated pest management (IPM) strategies. This study presents the first molecular identification of the dominant fruit fly species infesting chili (Capsicum annuum L.) in West Sumatra, Indonesia, using DNA barcoding of the mitochondrial cytochrome c oxidase subunit I (COI) gene. Adult specimens were collected between October 2024 and March 2025, and COI-specific primers were used to amplify the genomic DNA extracted from adult tissues. The resulting 685 bp sequences showed 99.0–99.4% similarity and 96–100% query coverage with reference sequences of Atherigona orientalis (e.g., accession codes PQ483146.1, PQ483144.1, EU627707.1) based on BLASTn analysis. Phylogenetic analysis using the Neighbor-Joining method further confirmed species-level identification by clustering the specimens within the A. orientalis clade with strong bootstrap support. This study provides the first molecular evidence of A. orientalis infestation in chili crops in West Sumatra. The findings offer new insights into the pest status of A. orientalis within chili agroecosystems and emphasize the need for targeted pest management strategies. Moreover, these results establish a valuable baseline for future studies on the host range, dispersal patterns, and seasonal dynamics of this emerging pest to support more effective mitigation planning.